2006
DOI: 10.1534/genetics.105.054767
|View full text |Cite
|
Sign up to set email alerts
|

A Mutation in Tac1p, a Transcription Factor Regulating CDR1 and CDR2, Is Coupled With Loss of Heterozygosity at Chromosome 5 to Mediate Antifungal Resistance in Candida albicans

Abstract: TAC1, a Candida albicans transcription factor situated near the mating-type locus on chromosome 5, is necessary for the upregulation of the ABC-transporter genes CDR1 and CDR2, which mediate azole resistance. We showed previously the existence of both wild-type and hyperactive TAC1 alleles. Wild-type alleles mediate upregulation of CDR1 and CDR2 upon exposure to inducers such as fluphenazine, while hyperactive alleles result in constitutive high expression of CDR1 and CDR2. Here we recovered TAC1 alleles from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
369
1
4

Year Published

2006
2006
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 350 publications
(384 citation statements)
references
References 49 publications
10
369
1
4
Order By: Relevance
“…2 and Table 4, each strain exhibiting trans-activation of MDR1 or CDR2 had increased levels of MDR1 mRNA or CDR2 mRNA, respectively. Strains exhibiting CDR2 trans-activation also coordinately overexpressed CDR1, as has been previously described for strains that contain hyperactive TAC1 alleles (9). This report focuses on the mechanism(s) whereby MDR1 is trans-activated in FLC R strains; mutations leading to trans-activation of CDR2 will be described in detail elsewhere.…”
Section: Phenotypic Characterization Of Flcmentioning
confidence: 77%
See 1 more Smart Citation
“…2 and Table 4, each strain exhibiting trans-activation of MDR1 or CDR2 had increased levels of MDR1 mRNA or CDR2 mRNA, respectively. Strains exhibiting CDR2 trans-activation also coordinately overexpressed CDR1, as has been previously described for strains that contain hyperactive TAC1 alleles (9). This report focuses on the mechanism(s) whereby MDR1 is trans-activated in FLC R strains; mutations leading to trans-activation of CDR2 will be described in detail elsewhere.…”
Section: Phenotypic Characterization Of Flcmentioning
confidence: 77%
“…Sanglard and coworkers identified a transcription factor, Tac1p, that binds an element within the CDR1/CDR2 promoter, the drug resistance element (DRE), and demonstrated its involvement in the high-level constitutive expression of these genes seen in some FLC R strains (10). Mutations within the TAC1 open reading frame (ORF) that lead to hyperactive trans-activation of CDR1 and CDR2 have been identified in FLC R strains (9). Therefore, mutations that result in increased activity of trans-activators occur commonly in FLC R strains.…”
mentioning
confidence: 99%
“…We have shown that Cap1p is likely to be one trans-acting factor for the HRE; however, confirmation of its role and the full identification of the trans-acting components with which it interacts will necessitate further investigation. Future studies will also clarify whether mutations in MCM1 can be responsible for high constitutive expression of MDR1 in a manner analogous to the recent finding that mutations in TAC1, a key trans-acting regulator of the ABC-transporter genes CDR1 and CDR2, are responsible for the high CDR1/ CDR2 expression of clinical strains (Coste et al, 2006).…”
mentioning
confidence: 75%
“…It was shown that the upregulation of the CDR1 and CDR2 genes in A r isolates is due to gain-of-function mutations in the zinc cluster transcription factor Tac1p (5,6). Most of these mutations consist of C-terminal amino acid substitutions or small inframe deletions (4,5).…”
mentioning
confidence: 99%